Особенности радиационного повреждения кремниевых детекторов высокоэнергетическими электронами - Маслов, Н.И.; Неклюдов, И.М. (Вопросы атомной науки и техники, 2002)
Damaging processes of silicon and silicon detectors, radiation damaging peculiarity of silicon and silicon detectors by conditions of electromagnetic showers development are considered in the work. Experimental results of silicon radiation damaging efficiency by electromagnetic showers, which are developed from initial electrons with energy 220, 500 and 1000 MeV are presented. Peculiarity of damages creation in detector was studied. It was shown, that radiation damaging efficiency in the bulk detector material may be different then radiation damaging efficiency in initial silicon with identical characteristics.